The Influence of the Marketing Mix of Animal Feed Products on Customer Satisfaction at PT Retailindo Anima Prakarsa, Makassar - Muhammad Amir; Megawhati Artiyani; Andi Tendean; Surya Kelana Basri; Mustalib (www.amertainstitute.com, 2026)
This study examines the influence of the marketing mix on customer satisfaction for animal feed products at PT Retailindo Anima Prakarsa, Makassar, Indonesia. In an increasingly competitive pet food retail market, an effective marketing mix strategy is essential to enhance customer satisfaction and maintain business sustainability. This research employs a mixed-method approach by integrating primary data obtained through questionnaires and interviews with secondary data from company documents and relevant literature. A total of 42 customers were selected using simple random sampling. The data were analyzed using descriptive statistics, simple linear regression, correlation analysis, coefficient of determination, and partial hypothesis testing (t-test). The results indicate that the marketing mix has a positive and significant effect on customer satisfaction. The regression model shows the equation Y = 4.61 + 0.90X, indicating that an improvement of one unit in the marketing mix increases customer satisfaction by 0.90 units. The correlation coefficient (r = 0.81) suggests a very strong relationship between the marketing mix and customer satisfaction, while the coefficient of determination (R² = 0.65) reveals that 65% of customer satisfaction is explained by the marketing mix variables, with the remaining 35% influenced by other factors. Furthermore, the t-test results confirm a significant effect (t-value = 8.74 > t-table = 1.68). These findings highlight the critical role of product availability, pricing strategy, promotion, distribution, and service quality in improving customer satisfaction. The study provides practical implications for retail managers in designing effective marketing strategies and contributes to empirical evidence in marketing mix studies within the animal feed retail sector.